Cross-sectional seroprevalence study of antibody to Bordetella pertussis toxin in western Saudi Arabia: is there a need for a vaccine booster dose for adolescents and young adults?. Issue 4 (8th April 2021) - Farahat, Fayssal; Althaqafi, Abdulhakeem; Al-Amri, Abdulfattah; Alsaedi, Asim; Abouremsh, Mohammad; Alshamrani, Majid
Abstract : Objectives: The present study was conducted to estimate the seroprevalence of antibody to pertussis toxin among adult populations in western Saudi Arabia. Design: A cross-sectional study. Setting: King Abdulaziz Medical City, Jeddah, western Saudi Arabia. A tertiary care teaching hospital. Participants: A total of 1200 participants (400 healthcare workers, 400 military recruits and 400 blood donors) were included. The majority were male (79.3%), and the mean (±SD) age was 27.2 (±6.7) years old. Interventions: The study included the analysis of serum blood samples using commercial ELISA. A consecutive sampling technique was applied. Primary outcome measures: Seropositivity of antipertussis toxin immunoglobulin G (anti-PT IgG) ≥62.5 IU/mL. Results: Antibody titres ≥62.5 IU/mL, indicating exposure to Bordetella pertussis infection within the last year, were identified in 12.0% (95% CI 10.2% to 14.0%) of the participants. Titres ≥125 IU/mL, suggesting recent infection, were detected in 3.5% (95% CI 2.5% to 4.7%). Seroprevalence of positive IgG antibody titres (≥62.5 IU/mL) was highest among the healthcare workers (HCWs) (14%), then the military recruits (13.5%) and blood donors (8.5%; p=0.03). The multivariate regression analysis showed association between participants group (HCWs and military), male gender and younger age (<25 years old) and higher antibody to pertussis toxin. Conclusions: High pertussis seropositivity was associated with participants' occupation (ie, healthcare workers and military recruits), and anti-PT IgG titre was negatively correlated with age. A substantial deficiency in pertussis reporting in Saudi Arabia has been suggested, with potential increased risk to the most vulnerable populations (ie, infants and elderly). Enhancing the booster dose of pertussis vaccine for adolescents and adults is crucial to minimise the burden of pertussis.